An evaluation of the U.P. College of Science Library facilities a users' perception - Bernal, Richard F.; Marzo, Ma. Arlene A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This paper focuses on two elements of performance of the library. These are technical and functional elements of performance deal with survival issues such as health, safety and security and performance of building systems. These elements can be characterized as the background environment for carrying out activities while the functional elements deal with fit between the building and the users' activities. The functional elements of a building support the activities carried out with it. They must be responsive to the specific needs of the organization and the occupants, both quantitative and qualitative. These elements for academic and research libraries are discussed in this study.
Published literature has been examined to review knowledge areas pertaining to the performance requirements of academic and research library facilities. A questionnaire was developed to obtain the users feedback on their experience with the library environment. The findings of the users' perceptions were analyzed and reported to describe the identified evaluation of the technical and functional performance of the existing facilities of the College of Science Library.
The suggested recommendations are the following: 1. Evaluate the facilities of the library using the PAARL standards guided by the results of this study; 2. Library facilities should be evaluated not only the reading areas but also on the other areas accessible by the users such as areas where the library materials are being kept; 3. Evaluate the facilities from the perceptions of CSLIB staff that can present more vital information regarding usage because they are also considered prime users of these facilities; 4. Signs are recommended to be used and displayed on emergency exists. Signs like "You are here" maps are also recommended to be displayed to direct the users to library support services, stairs, floor level and its contents, instruction messages, operation hours and contents of the entire library; and, 5. With reference to the crowdedness on the first level of the building, the management of CSLIB should devise creative means to make interior spaces on both level of the building better utilized and its occupancy to be maximized by its end users. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines College of Science Library; Library buildings -- Use studies